Pengembangan Kurikulum Pendidikan Agama Islam Multikultural Dalam Membangun Moderasi Beragama di UNISKA Kediri - Siti Sumadiyah; Sri Wahyuni (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
This study aims to develop an Islamic Religious Education (PAI) curriculum that incorporates multicultural values to foster religious moderation among students. The proposed curriculum integrates principles of cultural diversity and tolerance into PAI learning materials, allowing students to comprehend Islamic teachings while also appreciating and interacting harmoniously with adherents of other religions. Utilizing a qualitative research method with a phenomenological approach, this study addresses multicultural education as a relatively new phenomenon in PAI courses, emphasized as an essential competency for both lecturers and students. The phenomenological approach seeks to understand the daily lives and intersubjective experiences of the participants, aiming to reveal the meaning of concepts and phenomena as perceived by individuals. Conducted in a natural setting, this approach permits unrestricted interpretation of the phenomenon, granting researchers the freedom to analyze the data comprehensively. The findings indicate that a multicultural PAI curriculum effectively promotes an understanding of religious moderation among students and heightens awareness of the importance of multicultural perspectives in religion. These results are intended to guide educators and policymakers in creating a more inclusive PAI curriculum, thereby supporting the development of a peaceful and harmonious society.